Gay & grey: respectvolle bejegening, kun je dat leren: schriftelijke verantwoording - Bogaards, Paula; van der Dennen, Maureen; Dusault, Nicole (Eindhoven: Fontyshogeschool Eindhoven, 2003)
"Paula Bogaards, Maureen van der Dennen, Nicole Dusault... et al. Fonds Suzan Daniel (FSD)"